Single step combustion synthesis for the preparation of bismuth titanate ceramics for potential applications - Al-Amani, Umar; Srimala , Sreekantan; Ahmad Fauzi , Mohd Noor; Khairunisak, Abd Razak (Trans Tech Publications, Switzerland, 2013)
Bismuth titanate was systematically prepared by a single step combustion synthesis. Based on TG-DTA, the corresponding phase was completely obtained below 300oC, resulting in highly exothermic peak at 236oC. The formation of a single crystalline structure of Bi-layered with different degree of crystallinity was strongly affected by hydrolysis temperature. Goodness-of-fit indicator, S for entire samples was in the range of 1.55 – 1.94, which is acceptable for Rietveld refinement analysis. All Raman peaks became more intense and sharp with higher hydrolysis temperature, suggesting that the strong interactions between Ti-O bonding in BIT structure. The presence of peaks at 838 and 628 cm-1 in the IR spectrum can be ascribed to the stretching vibrations of Bi-O and Ti-O, respectively. Besides, the obtained powders are very fine with minimal grain growth, resulting in agglomerated powders.